Autologous white blood cell infusion for trauma, brain trauma, stroke and select immune dysfunction co-morbidities: A promising and timely proposal?. (August 2018) - Griffin, Gerald Dieter; Charron, Dominique; Al-Daccak, Reem
Abstract: All traumas suppress the immune system, resulting in higher morbidity and mortality. Infections, poor nutritional status, chronic illness, fatigue, therapies or procedures performed during and after transport also negatively affect the immune system. Large populations are impacted by trauma worldwide and suffer enormous costs in both direct and indirect expenditures from physical, psychological and functional losses. Most therapies and studies of trauma, brain trauma, stroke, immune suppression and their co-morbidities do not address nor discuss methods that promote immune system resuscitation or efficacy to support its role in post-trauma healing and rehabilitation. These omissions present an opportunity for using autologous stored naïve (unexposed to the current trauma and co-morbidities) white blood cell infusions (autologous white blood cell infusion) (AWBCI) to supplement treatment of most traumas, trauma-associated infections, other co-morbidities and immune suppression derived problems in order to improve the global standard of trauma care. We hypothesize to give the traumatized patients back their own immune system that has been 'stored' in some fashion, either cryogenically or just after or during the trauma event [surgery, etc for example]. We emphasize that other treatments should not be replaced – rather we suggest AWBCI as concurrent therapy. We present focused select animal and human studies as proofs of concept to arrive at and support our therapeutic suggestion and hypotheses, flowing historically from donor white blood cell therapy [DLI] to close cohort white blood cell therapy to autologous white blood cell infusion [AWBCI]. We integrate the concept of personalized medicine from an evidence-based framework while maintaining scientific rigor and statistical proof as a basis of our hypotheses.